Expression of KIR and C-type lectin receptors in Behcet's disease - (:unkn) unknown (OXFORD UNIV PRESS, 2004)
Objective. Behcet's disease (BD) is a multisystemic disorder with a possible underlying pathology of immune-mediated vasculitis. Genetic susceptibility associated with HLA-B*51 and B*2702 has been implicated in its pathogenesis. Considering the recently defined regulatory mechanisms of NK cells through HLA class I binding receptors, we hypothesized that interactions of NK and T cells through the NK receptors may be important in the pathogenesis of BD. Methods. The impact of different expression patterns of HLA-recognizing receptors on NK or T cells was analysed in 51 patients with BD and 32 healthy controls. We used flow cytometry to investigate the expression of KIR3DL1 from the polymorphic killer immunoglobulin-like receptor (KIR) family, which binds a shared HLA-Bw4 motif on HLA-B51 and *2702 alleles, and CD94 from the conserved C-type lectin receptor family, which binds HLA-E. Thirty-three of the BD patients and 19 of the controls carried the same HLA-Bw4 motif. Results. CD3(+). T cells were increased in patients with BD compared with controls (81 vs 75%, P = 0.001), whereas the NK cells did not show any difference between the two groups. Increased expression of CD94 in BD was observed on CD16(+)CD56(+) cells (66 vs 57, P = 0.04) and on CD3(+) (7.7 vs 4.0, P < 0.001) and CD3(+)CD56(+) (44 vs 35, P = 0.02) T cells. KIR3DL1 expression on the NK and T cells was not statistically different between the two groups. No effect of HLA-Bw4 motif was observed on the expression of CD94 and KIR3DL1 in both the patients and the controls. Conclusion. The absence of a correlation between KIR3DL1 expression and HLA-Bw4 motif confirms previous work reporting that the expression of these molecules is regulated separately. Increased expression of CD94 may suggest that NK receptors play a pathogenic or regulatory role in BD.
Keywords: Behet's disease; NK cell; KIR3DL1; CD94; HLA-B51; HLA-Bw4; HUMAN T-LYMPHOCYTES; HLA-B; INHIBITORY RECEPTORS; CELLS; RECOGNITION; MOLECULES; NKB1; PHENOTYPES; ACTIVATION; ARTHRITIS